Advances in Computer Science and Engineering 13th International CSI Computer Conference, CSICC 2008 Kish Island, Iran, March 9-11, 2008 Revised Selected Papers - Sarbazi-Azad, Hamid.; Parhami, Behrooz.; Miremadi, Seyed-Ghassem.; Hessabi, Shaahin. (Communications in Computer and Information Science,, 2009)
This book constitutes the revised selected papers of the 13th International CSI Computer Conference, CSICC 2008 held on Kish Island, Iran, in March 2008. The 84 regular papers presented together with 68 poster presentations were carefully reviewed and selected from a total of 426 submissions. The papers are organized in topical sections on learning/soft computing, algorithm theory, SoC and NoC, wireless/sensor networks, video processing and related topics, processor architecture, AI/robotics/control, medical image processing, p2p/cluster/grid systems, mobile ad hoc networks, web, signal processing/speech processing, misc, security, image processing applications as well as VLSI.